Analisis Biaya Dan Produktivitas Pemakaian Alat Berat Pada Kegiatan Pembangunan Jalan Akses Siak IV Pekanbaru - Nugraha, Devid; Iriana, Rian Trikomara; Djuniati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Road construction requires heavy equipment in its work, one of them is road layer. Heavy equipments which currently use is dump truck, excavator, motor greder, water tank truck, tandem roller and wheel loader. The number of heavy equipment to itemized work selected heap, Class B aggregate and A class aggregate are 1 unit excavator, 1 unit wheel loader, 15 unit dump trucks, 1 unit grader motor, 2 unit tandem rollers, 1 unit water tank, selected heap work which use the provisions of the owner is 9 days and the contractor 11 days, class B aggregate work using the provisions of the owner are 7 days and 9 days contractor, A class aggregate work using the provisions of the owner are 5 days and 7 days contractor. The differences in the cost of heavy equipment is Rp.121.650.532 or higher by using contractor's heavy equipment. To determine the heavy equipment with a more efficient cost with a saving percentage of 12.93% then, the contractor must meet the provisions made by the owner with the economical life tool, the condition of the machine and eligible labor.Keywords : Cost analysis, heavy equipment, productivity, road layer